RELATO DE EXPERIÊNCIA DE EDUCAÇÃO EM SAÚDE EM UM LAR DE ACOLHIMENTO - Cardoso, Kamila Pavelacki; Padilha, Milena Roberta Basso; Bones, Diovana Wagner; Bonamigo, Elenita Costa Beber; Rios, Karina Ribeiro; Pettenon, Marinez Koller (Salão do Conhecimento, 2017)
Projeto de extensão: Programa de Atenção à Saúde da Criança